Peran Masyarakat dalam Pencegahan dan Pemberantasan Tindak Pidana Korupsi - Risona Tarigan, Frandy; Sumodiningrat, Aprilian (Prodi Ilmu Hukum Fakultas Hukum Universitas Islam Jember, 2023)
The criminal act of corruption is an extraordinary crime, which can cause widespread damage to society, as stated in the preamble of the United Nations Convention Against Corruption (UNCAC). Corruption is a type of economic crime, where the losses suffered from this crime are related to the economy. This research is a doctrinal research using normative juridical method, as well as analytical descriptive. This study has two formulations of the problem, namely: first, what are the implications of corruption crimes on people's welfare?; Second, what is the role of the community in eradicating corruption? This research shows that: first, corruption crimes can greatly reduce the quality of people's lives, so that the eradication of corruption needs to be more enforced; secondly, much of the corruption that occurs in Indonesia is caused by a lack of social control, so that the role of society in eradicating corruption needs to be maximized as a means of controlling power.